EDUKASI PENGURANGAN NYERI HAID PADA REMAJA DENGAN INTEGRASI HOLISTIC CARE DAN KEARIFAN LOKAL - Hastutik, Hastutik; Noviani, Aris; Wigunantiningsih, Ana; Utami, Uji; Mahmudah, Mutik (LPPM POLBITRADA, 2025)
Dysmenorrhea or menstrual pain is a health complaint that is often experienced by adolescent girls in Indonesia. According to WHO, around 50-90% of adolescents experience menstrual pain that can hinder their learning and social activities. Although the intensity of the pain varies, this condition is often considered normal and receives little attention, even though it has an impact on the quality of life of adolescents. One way to overcome this complaint is through education, with a lecture method using leaflets containing natural and local wisdom-based methods to relieve pain. This activity was carried out for 29 grade XII female students at SMA Muhammadiyah I Karanganyar. Based on the results of the post-test, 24 female students (82.8%) showed a good level of knowledge.